Penyelarasan Strategi Bisnis dan Strategi Sistem/Teknologi Informasi untuk Peningkatan Kinerja Organisasi - Ardi Hamzah (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Alignment strategic become one of this topic in information system also represent the issue which stillnewly and interesting, especially its applying in Indonesia. System/ information technology proven have keeprole important in organizational development and existency. For that, needed aligment strategic model betweenstrategy of business and strategy of system/information technology in improving organizational performance.Strategic aligment for company to reach its target with the support of information system in process of businessto give the real correct management information. To this conduct, information technology at organization haveto in aligment with organizational goal. Emporwement and utilization of ability of system/informationtechnology inwroughtly, sinergy and comprehensive with organizational business strategy to reach for thecompetitif advantage assessed have given the significant contribution to organizational strategic aligment. Morehigh level strategic aligment between strategy of business and strategy of system/information technology,organizational will instruct the information system of matter of crucial to reach for the successful businessperformance.Keywords: aligment strategic, strategy of business, strategy of system/information technology.